P146: Does a communications skills intervention improve emergency department staff coping skills and burnout?. (May 2019) - Zhou, F.; Howlett, M.; Talbot, J.; Fraser, J.; Robinson, B.; Atkinson, P.
Abstract : Introduction : Emergency department (ED) staff carry a high risk for the burnout syndrome of increased emotional exhaustion, depersonalization and decreased personal accomplishment. Previous research has shown that task-oriented coping skills were associated with reduced levels of burnout compared to emotion-oriented coping. ED staff at one hospital participated in an intervention to teach task-oriented coping skills. We hypothesized that the intervention would alter staff coping behaviors and ultimately reduce burnout.Methods : ED physicians, nurses and support staff at two regional hospitals were surveyed using the Maslach Burnout Inventory (MBI) and the Coping Inventory for Stressful Situations (CISS). Surveys were performed before and after the implementation of communication and conflict resolution skills training at the intervention facility (I) consisting of a one-day course and a small group refresher 6 to 15 months later. Descriptive statistics and multivariate analysis assessed differences in staff burnout and coping styles compared to the control facility (C) and over time.Results : 85/143 (I) and 42/110 (C) ED staff responded to the initial survey. Post intervention 46 (I) and 23(C) responded. During the two year study period there was no statistically significant difference in CISS or MBI scores between hospitals (CISS: (Pillai's trace = .02, F(3, 63) = .47, p = .71, partial η2 = .02); MBI: (Pillai's trace = .01, F(3, 63) = .11, p = .95, partial η2 = .01)) or between pre- and post-intervention groups (CISS: (Pillai's trace = .01, F(3, 63) = .22, p = .88, partial η2 = .01); MBI: (Pillai's trace = .09, F(3, 63) = 2.15, p = .10, partial η2 = .01)).Conclusion : We were not able to measure improvement in staff coping or burnout in ED staff receiving communication skills intervention over a two year period. Burnout is a multifactorial problem and environmental rather than individual factors may be more important to address. Alternatively, to demonstrate a measurable effect on burnout may require more robust or inclusive interventions.